The paradox of diversity in leadership and leadership for diversity - Bebbington, Diane; Özbilgin, Mustafa (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2013)
The paradox of diversity is that successful diversity interventions require leadership support when diversity in leadership positions is so evidently lacking. In order to explore this paradox in the UK, we examine progress towards demographic diversity in leadership roles in the higher education sector, a sector in which there is much espoused support for diversity. Through a critical and comprehensive review of the literature, we illustrate the persistent nature of inequalities that hinder diversity and inclusion in leadership. We examine studies on salient forms of inequality in higher education leadership including research on gender, ethnicity, class, sexual orientation and disability. We show that leadership diversity remains a significant challenge for the higher education sector. Drawing on the example of this sector, we demonstrate that leadership occupies a contradictory space in terms of demographic diversity, both as the focus of criticism due to its homogeneous profile and counter-intuitively as an essential force for progress towards greater equality. We investigate the paradox of the relative homogeneity of higher education leadership set against its role for championing and promoting equality and identify ways in which demographic diversity as well as the progressive potential of higher education leadership may be fostered.